Free and for all? A comparative study of programs with user fees in North American and Danish public libraries. Issue 2 (7th March 2020) - Lenstra, Noah; Mathiasson, Mia Høj
Abstract : Purpose: As a research topic within the field of LIS, programs in public libraries are underexplored, and the question of user fees for programs has not previously been addressed. Design/methodology/approach: This article compares data collected from two individually conducted studies of public library programs in North America and Denmark to enrich our understanding of user fees in relation to programs. Findings: The comparative analysis shows both similarities and deviations regarding the levying of fees for library programs. While paying a fee to attend a program is rather normal in Denmark, it is more of a fringe idea in North America. Research limitations/implications: By exploring a previously understudied facet of contemporary public librarianship, this article opens up new avenues for inquiry regarding how the relative accessibility and availability of programs relate to theoretical discussions about programs as public library services. Practical implications: This article provides library managers with needed information about how to conceptualize the roles of programs as public library services. Social implications: As programming surges to the fore in contemporary public librarianship, the levying of user fees has social implications in terms of social equity and the public library ethos of free and equal access for all. Originality/value: This article is the first study of user fees for public library programs, as well as among the first cross-national comparisons of programming as a dimension of public librarianship.